Laurdan and Di-4-ANEPPDHQ probe different properties of the membrane - Amaro, Mariana; Reina, Francesco; Hof, Martin; Eggeling, Christian; Sezgin, Erdinc (Journal of physics D: Applied physics, 2017)
Lipid packing is a crucial feature of cellular membranes. Quantitative analysis of membrane lipid packing can be achieved using polarity sensitive probes whose emission spectrum depends on the lipid packing. However, detailed insights into the exact mechanisms that cause the changes in the spectra are necessary to interpret experimental fluorescence emission data correctly. Here, we analysed frequently used polarity sensitive probes, Laurdan and di-4-ANEPPDHQ, to test whether the underlying physical mechanisms of their spectral changes are the same and, thus, whether they report on the same physico-chemical properties of the cell membrane. Steady-state spectra as well as time-resolved emission spectra of the probes in solvents and model membranes revealed that they probe different properties of the lipid membrane. Our findings are important for the application of these dyes in cell biology.
Keywords: laurdan; di-4-ANEPPDHQ; liposomes; GPMVs; time-dependent fluorescence shift; lipid packing; cell membrane